Atuação do Pedagogo em espaços não escolares: um estudo de caso no CRAS de Campos Belos - GO - Cruz, Ynaiá Aires França Santa (Universidade Federal do Tocantins, 2022)
Pedagogy is sometimes associated with the environment, but little is explored and discussed about the performance of professional pedagogues in other environments. The present work aims to investigate the different fields of activity of Pedagogy in non-school spaces, that is, beyond the performance in the classroom. The specific objectives are: to identify the role that professional pedagogues develop in non-school spaces, research the importance of Pedagogues working in non-school institutions and describe the main challenges faced in these spaces. To carry out this study, bibliographic research was used, with data collected from secondary sources (books, magazines, periodicals and websites) among others. Authors such as Brandão (2007), Cagliari (2009), Freire (2011), Libâneo (2001), Oliveira (2012), Santos (2015), Saviani (1985), Kochhann (2021) among others were part of the foundation of this work. The research also included the field study, data were collected through semi-structured interviews on the aforementioned theme. Therefore, this study brings results from research by theorists who have dedicated themselves to discussing the subject, from their experiences, provides information and reflections about the role of the pedagogue in these spaces, providing knowledge in the performance in this area, promoting good relationships with all professionals who are inserted in this same environment, as well as other sectors, thus contributing to the important work that is intended for people who are users of CRAS programs. Through field research, it was observed the work that the pedagogue performs in other environments that go beyond the school wall. This work is organized in different time, form and spaces, but it is just as important as that developed at school.